2009
DOI: 10.1124/jpet.109.155424
|View full text |Cite
|
Sign up to set email alerts
|

Immunoneutralization of Agmatine Sensitizes Mice to μ-Opioid Receptor Tolerance

Abstract: Systemically or centrally administered agmatine (decarboxylated arginine) prevents, moderates, or reverses opioid-induced tolerance and self-administration, inflammatory and neuropathic pain, and sequelae associated with ischemia and spinal cord injury in rodents. These behavioral models invoke the N-methyl-D-aspartate (NMDA) receptor/nitric-oxide synthase cascade. Agmatine (AG) antagonizes the NMDA receptor and inhibits nitric-oxide synthase in vitro and in vivo, which may explain its effect in models of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Besides, agmatine could also revert the change of anti-inflammatory cytokines, such as IL-4 and IL-10 [108]. In addition, the anti-inflammatory effect of agmatine was also proved in many other neurological diseases, such as transient brain ischemia, depression, TBI and micro-opioid receptor tolerance, by regulating the expression of inflammatory cytokines [22, 109].…”
Section: Neuroprotective Properties Of Agmatine In Neurological Diseasesmentioning
confidence: 99%
“…Besides, agmatine could also revert the change of anti-inflammatory cytokines, such as IL-4 and IL-10 [108]. In addition, the anti-inflammatory effect of agmatine was also proved in many other neurological diseases, such as transient brain ischemia, depression, TBI and micro-opioid receptor tolerance, by regulating the expression of inflammatory cytokines [22, 109].…”
Section: Neuroprotective Properties Of Agmatine In Neurological Diseasesmentioning
confidence: 99%
“…Numerous studies have shown enhanced antinociceptive effects of opioids when used in combination with NMDA antagonists, suggesting analgesic synergism [13][14][15][16][17][18]. Additionally reduced tolerance development to morphine and other μ-opioids has been obtained by combination with NMDA receptor antagonists [19][20][21][22][23][24][25]. Antinociceptive effects of intrathecally administered EM-1 can be significantly enhanced in a synergistic fashion by NMDA antagonists [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been measured in animal tissues and found to be present in whole lung homogenates, but this does not exclude the contribution of serum agmatine [18] . Finally, agmatine is a known α2-adrenoreceptor and imidazoline receptor agonist with suggested roles including vasodilation and the prevention of opioid induced tolerance [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%